The implementation of Precision Teaching for the improvement of academic skills: A systematic review of the literature over thirty years. (27th December 2021) - Tiernan, Aoife Mc; McCoy, Anna; Mendonca, Jamima; Lydon, Helena; Diffley, Shauna
Abstract: Precision Teaching (PT) is a system for precisely defining, measuring and facilitating the subsequent analysis, interpretation, and decision making behavior (Kubina & Yurich, 2012). It can be incorporated into educational settings to monitor learners' progress and evaluate the effectiveness of teaching approaches for academic skills. The current systematic review provides a summary of studies published over 30 years which implemented PT for the improvement of academic skills. Key components of PT as implemented across studies are summarized. The findings of this review are discussed in relation to future research, identifying gaps in the literature and suggesting areas for improvement and further research on PT.